2012
DOI: 10.1007/s11250-012-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genotyping of Mycobacterium bovis isolated from cattle tissues in the North West Region of Cameroon

Abstract: An epidemiological study was carried out to determine the Mycobacterium bovis strains causing bovine tuberculosis (TB) in cattle in North West Cameroon. Suspected TB lesions from slaughtered cattle were cultured on Lowenstein-Jensen and Middlebrook 7 H9 media to isolate mycobacteria agents for molecular genotyping using deletion analysis and spoligotyping. PCR-based genomic deletion typing showed that 54 of 103 tubercle bacilli isolated from cattle tissue were M. bovis strains and the African 1 clonal complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The most prevalent spoligotypes were SB0944 and SB0953 which is consistent with previous studies in Cameroon 16, 17, 39 . Interestingly, although a recent study revealed that SB0944 was the most predominant spoligotype, the second most predominant spoligotype was SB0955 16 and not SB0953 as in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most prevalent spoligotypes were SB0944 and SB0953 which is consistent with previous studies in Cameroon 16, 17, 39 . Interestingly, although a recent study revealed that SB0944 was the most predominant spoligotype, the second most predominant spoligotype was SB0955 16 and not SB0953 as in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first report of SB0120 with an Af1 chromosomal deletion, the details and implication of which will be explored at a later date. In general, the distribution and population structure of M. bovis clonal complexes superficially appears to have remained consistent with earlier reports 16, 17, 39 , but this fails to capture the details revealed by higher resolution analysis.…”
Section: Discussionsupporting
confidence: 75%
“…Overall 43.1% (162/376) of samples were confirmed positive by PCR from the presumptive positive cultures. The results showed a high prevalence of MTBC when compared to other reported studies, for example Awah-Ndukum et al (2013) reported an MTBC frequency of 1.6% isolated from slaughtered cattle in Cameroon, and Müller et al (2008) reported a frequency of 1.8% from slaughtered cattle in Mali.…”
Section: Discussionmentioning
confidence: 42%
“…In areas where bovine Tb is endemic and not controlled or partially controlled, human Tb due to M. bovis may occur resulting from ingesting contaminated fresh milk and meat products and by inhaling cough spray from infected cattle [ 3 – 8 ]. Widespread bovine Tb in cattle has been diagnosed in some parts of Cameroon following comparative cervical tuberculin test, detection of Tb lesions during abattoir slaughter meat inspection, acid fast staining of bacilli, and molecular analysis of cultured isolates [ 1 , 9 , 10 ]. Also, M. bovis in human has been reported in the West and Northwest Regions of Cameroon [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%